Gumilëvskie čtenija - Martynov, V. F. (Wiener Slawistischer Almanach - Sonderbaende, 1984)
n 1975 a group of Leningrad poets sought official permission to hold a memorial meeting commemorating the ninetieth anniversary of the birth of Nikolaj Stepanovič Gumilev (1886 -1921) the following year, as well as issuing a collection of their poetry. On April 16. 1976 the poet Oleg Oxapkin and the historian Vladimir Poreš initiated the first memorial meeting devoted to the founder of Acmeism. Since that time there have been three additional "unofficial conferences" held (1978, 1979 and 1980). At these yearly private meetings, literary historians, poets and poetry lovers converge and pay homage to Gumilev. The section containing material relating to Gumilev in this volume is significant and illuminating.